Pengaruh Work Pressure, Kelelahan Kerja terhadap Kinerja Karyawan dengan Stres Kerja sebagai Mediasi, Sektor Farmasi - Syifa Aulia; Nadia Hamidah Putri; Zain Atikah Pramudita; Sri Wahyuni (MAMEN: Jurnal Manajemen, 2025)
The increasingly competitive job market has heightened work pressure faced by employees, particularly in the pharmaceutical sector. Unmanaged work pressure can lead to stress and job burnout, ultimately resulting in decreased employee performance. This study aims to analyze the effects of work pressure, job stress, and job burnout on employee performance in a pharmaceutical company. A quantitative method was employed, using a semi-structured questionnaire distributed to 50 purposively selected respondents. The study focused on testing seven hypotheses that include both direct and mediating relationships among the variables. Literature review indicates that work pressure and job stress have direct impacts on job burnout and employee performance. Furthermore, job burnout acts as a mediating variable in the relationship between work pressure, job stress, and performance. These findings highlight the importance of managing work pressure and stress to maintain optimal employee performance, as well as the need for leadership and organizational support in fostering a healthy work environment.